2016
DOI: 10.3390/rs8080654
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Effects of Wildfire on Permafrost Distribution in Interior Alaska Derived from Remote Sensing

Abstract: Climate change coupled with an intensifying wildfire regime is becoming an important driver of permafrost loss and ecosystem change in the northern boreal forest. There is a growing need to understand the effects of fire on the spatial distribution of permafrost and its associated ecological consequences. We focus on the effects of fire a decade after disturbance in a rocky upland landscape in the interior Alaskan boreal forest. Our main objectives were to (1) map near-surface permafrost distribution and drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
(68 reference statements)
3
33
0
Order By: Relevance
“…Fire is the dominant disturbance mechanism in boreal forests (Stocks et al, 2002), and shifts in future fire regimes are likely to alter forest dynamics including vegetation composition (Johnson, 1992;Johnstone et al, 2010;Payette, 1992;Viereck, 1973) and carbon cycling (Balshi et al, 2009b;Genet et al, 2013). Boreal fires initiate both positive (+) and negative (−) climate feedbacks by emitting greenhouse gases (+; Amiro et al, 2001;Bond-Lamberty, Peckham, Ahl, & Gower, 2007) and carbonaceous aerosols during combustion (+ and −;Flanner, Zender, Randerson, & Rasch, 2007;Mouteva et al, 2015;Ward et al, 2012), reaccumulating carbon during postfire regrowth (−; Alexander & Mack, 2016;Amiro et al, 2010;Goulden et al, 2011), degrading permafrost which releases CO 2 and CH 4 (+; Brown et al, 2016;Jafarov, Romanovsky, Genet, McGuire, & Marchenko, 2013;Jorgenson et al, 2010), and altering the surface energy balance, primarily through albedo (−; Amiro et al, 2006;French, Whitley, & Jenkins, 2016;Randerson et al, 2006;Rogers, Randerson, & Bonan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fire is the dominant disturbance mechanism in boreal forests (Stocks et al, 2002), and shifts in future fire regimes are likely to alter forest dynamics including vegetation composition (Johnson, 1992;Johnstone et al, 2010;Payette, 1992;Viereck, 1973) and carbon cycling (Balshi et al, 2009b;Genet et al, 2013). Boreal fires initiate both positive (+) and negative (−) climate feedbacks by emitting greenhouse gases (+; Amiro et al, 2001;Bond-Lamberty, Peckham, Ahl, & Gower, 2007) and carbonaceous aerosols during combustion (+ and −;Flanner, Zender, Randerson, & Rasch, 2007;Mouteva et al, 2015;Ward et al, 2012), reaccumulating carbon during postfire regrowth (−; Alexander & Mack, 2016;Amiro et al, 2010;Goulden et al, 2011), degrading permafrost which releases CO 2 and CH 4 (+; Brown et al, 2016;Jafarov, Romanovsky, Genet, McGuire, & Marchenko, 2013;Jorgenson et al, 2010), and altering the surface energy balance, primarily through albedo (−; Amiro et al, 2006;French, Whitley, & Jenkins, 2016;Randerson et al, 2006;Rogers, Randerson, & Bonan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the dominance of energy balance changes may seem to contradict the strong sensitivity of modeled thaw dynamics to hydrological parameters (Figures and ), these results are reconciled by noting that heat transport via advection is a function of both the energy content of groundwater (a function of soil temperature) and the magnitude of groundwater flow (a function of recharge and active layer thickness). Therefore, changes in the energy balance can be the dominant driver of permafrost thaw dynamics as observed in previous studies (Brown et al, ), even where groundwater flow is an important process. As warming in high‐latitude regions shifts the timing and magnitude of spring snowmelt, changes in to the water balance may increase in importance (Bring et al, ; Lique et al, ), in particular at sites with finer‐grained mineral soils which are able to hold more unfrozen water even at subzero temperatures, buffering permafrost from changes in air temperature (Nicolsky & Romanovsky, ).…”
Section: Discussionmentioning
confidence: 55%
“…Increases in active layer thickness following fire occur via two mechanisms: (1) thinning the near‐surface organic soil layer which acts as a thermal buffer between air and the subsurface (Brown et al, , ; Kasischke & Johnstone, ) and (2) decreasing albedo which increases energy input into the subsurface (Rocha & Shaver, ; Smith et al, ; Yoshikawa et al, ). Past modeling efforts studying postfire active layer thickness have primarily concluded that soil thermal properties are the most important control on permafrost response to fire (Jiang et al, ; Jiang, Rastetter, et al, ; Yi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic Aperture Radar (SAR) has become an essential tool for the rapid analysis of, for example, disaster monitoring [1], maritime monitoring and land cover changes [2,3] including environmental monitoring [4]. Especially for a large-scale deformation, interferometric analysis (InSAR) in a wide-swath observation mode is effective for precisely detecting ground displacement [5].…”
Section: Introductionmentioning
confidence: 99%